Effects of kinesiotherapy on muscle strengthening in patients with Parkinson disease - Edina Tanović; Adnana Talić-Tanović; Jasminka Ðelilović-Vranić; Amir Rekić; Adnan Papović; Emina Tanović (Medicinski glasnik, 2018)
Aim: To investigate the effect of kinesiotherapy on muscle strengthening in patients with Parkinon's disease. Methods: This clinical retrospective-prospective study was based on collected data from medical histories and included 40 patients, who, beside medicaments, had undergone kinesiotherapy. This study analysed age, gender, duration of the rehabilitation and estimation of the gross muscle strength at admittance and discharge using Manual Muscle Test (MMT). Results: Females was slightly more represented in the total sample without significant statistical difference. After kinesiotherapy significant statistical difference in muscle strength was observed, average MMT of the upper extremities increased from 3.25±0.6 to 3.53±0.8 and on the lower extremities from 2.9±0.8 to 3.3±0.9. The analysis of the gender on the higher score of MMT showed that gender does not affect the score of MMT. Correlational analysis of the age and duration of hospitalization on the score of MMT showed that patients with longer hospitalization had better improvement. Conclusion: Results: of the study showed that kinesiotherapy has positive effect on muscle strength in patients with Parkinson's disease.
Keywords: rehabilitation; hospitalization; manual muscle test (MMT)